Evaluation of Different Approaches to Capital Structure Regulation - Stephan Schaeffler (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2012)
With the introduction of incentive regulation in many network industries, different approaches how to remunerate invested capital have been used. Under incentive regulation, many regulators remunerate the regulated asset base with a weighted average cost of capital (WACC) based on a pre-defined gearing, not considering individual capital structure at all. From a regulator's point of view, the aim is clear: Provide incentives to the firms to optimize their capital structure, i.e. finding the right balance between equity financing and debt. Taggert (1981) shows that rate-of-return regulation creates an incentive for regulated firms to alter their capital structures in order to influence consumer prices. Spiegel and Spulber (1994) find that the firm chooses its equity and debt in order to affect the outcome of the regulatory process. As a hybrid model between WACC and individual capital structure, the German Regulator sets incentives for a certain capital structure by limiting the return on equity that can be incorporated into network tariffs with a cap. However it has not been analyzed neither in theoretical nor in practical research which incentives are really created by this cap. To analyze the impact of different capital structure regulation mechanisms on the optimal capital structure, a static trade-off-theory model of capital structure is presented and the characteristics of several different approaches to capital structure regulation and their characteristics are analyzed. The results indicate that the overall effect of capital structure regulation is very important: In an ex-ante regulation setting, the consideration of individual capital structures leads to higher equity ratios than the use of a benchmark-WACC. In this context, caps are an effective mean to set incentives for a predefined equity ratio. In an ex-post regulation where bankruptcy is merely a threat, it may be optimal to rely on extreme strategies solely financing with equity or debt.
Keywords: G32; G38; L9; 330; Capital structure; trade-off theory; network operators; regulation; cost of equity